TLR activation, immune response and viral protection elicited in cattle by a commercial vaccine against Bovine Herpesvirus-1 - Kornuta, Claudia Alejandra (2021)
The innate and acquired immune response induced by a commercial inactivated vaccine against Bovine Herpesvirus-1 (BoHV-1) and protection conferred against the virus were analyzed in cattle. Vaccination induced high levels of BoHV-1 antibodies at 30, 60, and 90 days post-vaccination (dpv). IgG1 and IgG2 isotypes were detected at 90 dpv, as well as virus-neutralizing antibodies. An increase of anti-BoHV-1 IgG1 in nasal swabs was detected 6 days post-challenge in vaccinated animals. After viral challenge, lower virus excretion and lower clinical score were observed in vaccinated as compared to unvaccinated animals, as well as BoHV-1-specific proliferation of lymphocytes and production of IFNγ, TNFα, and IL-4. Downregulation of the expression of endosome Toll-like receptors 8–9 was detected after booster vaccination. This is the first thorough study of the immunity generated by a commercial vaccine against BoHV-1 in cattle.